POPULATION MANAGEMENT OF STREET DOGS IN INDIA: LEGAL FRAMEWORK & CHALLENGES - Dighe, Poorva; VS, Dr. Gigimon (South Eastern European Journal of Public Health, 2025)
A dog is regarded as a man’s best friend and for centuries, humans and dogs have lived together harmoniously. Dogs are the most commonly kept domesticated species of companion animals who thrive in and around human civilizations. The increasing population of dogs, both pets and strays, can foster negative interactions between humans and dogs thereby creating considerable risks for humans and raising welfare concerns for dogs. Aggressive behavior, dog bites, and the spread of diseases particularly rabies are the major factors that affect human beings whereas, cruelty to dogs and their illegal culling are the major concerns affecting the welfare of dogs. According to the Ministry of Health and Family Welfare, incidents of dog bites in India have increased from 21.80 lakhs in 2022 to 27.59 lakhs in 2023. Furthermore, according to the World Health Organisation, India contributes to one-third of the total deaths due to rabies, out of which nearly ninety-seven percent are transmitted through dogs and cats. On the other hand, increased conflicts, diminutive punishments under the Prevention of Cruelty to Animals Act, 1960, poor implementation of Animal Birth Control Rules, and lack of sensitization of people on animal welfare and allied laws, have resulted in a sharp increase in the instances of brutality, cruelty, and killing of street dogs. Last year, the Kunnur District Panchayat even filed a petition before the Supreme Court of India to euthanize ‘suspected rabid dogs’ and ‘extremely dangerous stray dogs’. Through this paper, the researcher analyses the major factors contributing to the increased population of dogs, the legal framework, guidelines, and judicial decisions in India regarding the population management of dogs, and the possible solutions for tackling the human-dog conflict keeping in the welfare of both groups.